Desain dan implementasi sistem pemantauan kualitas udara berbasis IoT di perkotaan - Aziz, Sulton Abdul (Maliki Interdisciplinary Journal, 2024)
Poor air quality in cities is a serious environmental problem and has a direct impact on public health. With the development of Internet of Things (IoT) technology, air quality monitoring can be done in real-time and efficiently. This article describes the design and implementation of an IoT-based air quality monitoring system in urban areas. This system uses sensors to detect air quality parameters such as PM2.5, PM10, CO, NO2, and SO2, and sends the data wirelessly to a central server for analysis and visualization. The trial results show that this system is able to provide accurate data and can be accessed via a web application, helping the government and society take appropriate action to improve air quality.